Analysis of masonry walls subjected to high strain rate out-of-plane loads with a rate dependent interface model - Rafsanjani, Seyedebrahim Hashemi (2014)
Masonry is a composite material composed of individual units laid in and bound together by mortar. Appropriate Understanding of masonry material properties results in secure and efficient protection and strengthening of historical structures. Due to high computation costs and difficulties deal with detailed modelling of masonry structures, few studies are available in open literature dedicated to micro numerical modelling of masonry structures subjected to blast loading. In present study, the objective is to propose a dynamic interface model obeying non-associated flow rule with high strain rate effects to apply as material model for interface elements. In order to introduce the strain rate effects of brick and mortar properties, a recent developed model is applied here. Verifying the capability of the model proposed, numerical simulations are carried out to investigate the behaviour of unreinforced brick masonry walls subjected to explosive blast loading by using the finite element (FE) code ABAQUS. The results obtained are compared with field test data to find good agreement. A comprehensive parametric analysis is finally accomplished with different main material properties to evaluate the effect of each parameter on high strain rate response of masonry walls.